Effects of Improv Training on Older Adults in a Long Term Care Facility. (May 2021) - Lindquist, Lee A.; Liggett, Anna; Muhammad, Ruqayyah; Seltzer, Anne; Kim, Kwang-Youn A.; Barish, Becca; Wagner, Abby; Ramirez-Zohfeld, Vanessa
Adjusting to life in a long term care facility (LTCF) can be challenging for older adults. Improvisation (shortened to improv) is a unique activity that encourages creativity and adaptive cognitive stimulation, through performing short scenes with content suggestions. We sought to assess whether improv training, in the form of a course entitled Humor Doesn't Retire (HDR), could impact patient-centered outcomes in a LTCF. About 15 adults (mean age 83.6 years) living in a LTCF participated in the 8-week HDR course with pre and 1-month post mixed method surveys assessing validated Patient Reported Outcomes Measurement Information System (PROMIS) measures and qualitative open-ended responses. Participants experienced significant improvements in social isolation and perceived stress ( p  < .05), and trend improvements in positive affect, self-efficacy, and anxiety. Participants described themes of increased attentiveness, becoming more relaxed, increased cognitive stimulation, and improved communication skills. In conclusion, LTCFs may want to consider offering improv training to positively improve the lives of older adult residents.